Botanicals as a zinc oxide alternative to protect intestinal cells from an Escherichia coli F4 infection in vitro by modulation of enterocyte inflammatory response and bacterial virulence - Bonetti, Andrea; Piva, Andrea; Grilli, Ester (Frontiers in Veterinary Science, 2023)
Pharmacological doses of zinc oxide (ZnO) have been widely used in pig industry to control post-weaning diarrhea (PWD) symptoms exacerbated by enterotoxigenic Escherichia coli F4 infections. Because of environmental issues and regulatory restrictions, ZnO is no longer sustainable, and novel nutritional alternatives to manage PWD are urgently required. Botanicals represent a wide class of compounds employed in animal nutrition because of their diverse beneficial functions. The aim of this study was to investigate the in vitro protective action of a panel of essential oils and natural extracts on intestinal Caco-2 cells against an E. coli F4 infection. Moreover, we explored the potential mechanisms of action of all the botanicals compared to ZnO. Amongst the others, thyme essential oil, grape seed extract, and Capsicum oleoresin were the most effective in maintaining epithelial integrity and reducing bacterial translocation. Their mechanism of action was related to the modulation of cellular inflammatory response, the protection of tight junctions’ expression and function, and the control of bacterial virulence, thus resembling the positive functions of ZnO. Moreover, despite their mild effects on the host side, ginger and tea tree essential oils provided promising results in the control of pathogen adhesion when employed during the challenge. These outcomes support the advantages of employing selected botanicals to manage E. coli F4 infections in vitro, therefore offering novel environmentally-friendly alternatives to pharmacological doses of ZnO capable to modulate host-pathogen interaction at different levels during PWD in pigs.